2018
DOI: 10.1186/s12610-018-0070-6
|View full text |Cite
|
Sign up to set email alerts
|

Sperm aneuploidy and DNA fragmentation in unexplained recurrent pregnancy loss: a multicenter case-control study

Abstract: BackgroundRecurrent pregnancy loss (RPL) is defined as the loss of at least three pregnancies in the first trimester. Although the most common cause is embryo aneuploidy, and despite female checkup and couple karyotyping, in about 50% of cases RPL remain unexplained. Male implication has little been investigated and results are discordant. In this context, we conducted a multi-center prospective case-control study to investigate male gamete implication in unexplained RPL.MethodsA total of 33 cases and 27 contr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
35
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(37 citation statements)
references
References 31 publications
1
35
0
Order By: Relevance
“…In recent years, the paternal contribution to RPL and RIF beyond semen parameters and karyotyping is being increasingly examined. Multiple studies suggest that increased levels of sperm aneuploidy may be a significant contributory factor in RPL and/or RIF (Rubio et al 2001, Carrell et al 2003, Bernardini et al 2004, Collodel et al 2009, Rubio et al 2009, Neusser et al 2015, Ramasamy et al 2015, Zidi-Jrah et al 2016, Esquerre-Lamare et al 2018. These studies have reported a two-to seven-fold increase in sperm aneuploidy for the investigated chromosomes in these patients (Fig.…”
Section: Sperm Aneuploidy and Recurrent Pregnancy Loss (Rpl) And Art mentioning
confidence: 87%
See 1 more Smart Citation
“…In recent years, the paternal contribution to RPL and RIF beyond semen parameters and karyotyping is being increasingly examined. Multiple studies suggest that increased levels of sperm aneuploidy may be a significant contributory factor in RPL and/or RIF (Rubio et al 2001, Carrell et al 2003, Bernardini et al 2004, Collodel et al 2009, Rubio et al 2009, Neusser et al 2015, Ramasamy et al 2015, Zidi-Jrah et al 2016, Esquerre-Lamare et al 2018. These studies have reported a two-to seven-fold increase in sperm aneuploidy for the investigated chromosomes in these patients (Fig.…”
Section: Sperm Aneuploidy and Recurrent Pregnancy Loss (Rpl) And Art mentioning
confidence: 87%
“…These studies have reported a two-to seven-fold increase in sperm aneuploidy for the investigated chromosomes in these patients (Fig. 3) (Collodel et al 2009, Kohn et al 2016, Zidi-Jrah et al 2016, Esquerre-Lamare et al 2018. The majority of the aforementioned studies have focused on males with reduced semen parameters; however, a large study reported that up to 40% of male partners of RPL with normal semen parameters also had significantly increased sperm aneuploidy levels (Ramasamy et al 2015).…”
Section: Sperm Aneuploidy and Recurrent Pregnancy Loss (Rpl) And Art mentioning
confidence: 98%
“…The rates of abnormal sperm morphology and sperm DNA fragmentation have been reported to be significantly increased in patients with repeated abortions compared with those of fertile men without ART treatments (Esquerré‐Lamare et al, 2018; Kamkar, Ramezanali, & Sabbaghian, 2018; Zidi‐Jrah et al, 2016). A meta‐analysis review showed that the NSMR was decreased among men with unexplained repeated abortions compared with the control group (Cao et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…For example, some studies report that up to 40% of men from couples with recurrent pregnancy loss had normal sperm density and motility, but had sperm aneuploidy [17]. While the role and degree of sperm DNA defects are controversial [18], there are examples where, even with normal semen analysis, men can have sperm with abnormal components.…”
Section: Men Are As Likely As Women To Be Responsible For Infertilitymentioning
confidence: 99%